Identifikasi Prinsip Ekowisata Pada Pengembangan Desa Wisata Cibeusi, Kabupaten Subang - Doni Riswandi; Gina Puspitasari Rochman (UNISBA Press, 2023)
Abstract. The variety of potentials owned by Cibeusi Village makes a high selling point for the tourism sector. Cibeusi Village has abundant natural and cultural potential. This potential can be used as a tourist attraction for the development of tourist villages. In addition, the development of tourism in Cibeusi Village, on the other hand, is the conversion of agricultural land into tourism activities such as stalls, recreation areas and lodging or the influence of tourists that damage environmental sustainability. On the other hand, Cibeusi Village has a wealth of biological resources in the form of flora and fauna and natural beauty due to there being tours and there are also resources that must be protected and preserved in their beauty. Thus, it is necessary to study the identification of ecotourism principles, from the description of the problem raises research questions in Cibeusi Village, namely